Entrepreneurial Strategy of Pastry MSMEs: The Effect of Product, Price, and Promotion on Sales Performance - Marwan Effendi; Yuliani Yuliani (Jurnal Kewirausahaan dan Bisnis, 2026)
Increasing competition among micro, small, and medium enterprises (MSMEs) in the culinary sector requires entrepreneurs to formulate effective entrepreneurial strategies to sustain business performance. This study examines the effect of product, price, and promotion as entrepreneurial strategic decisions on the sales performance of pastry MSMEs in Kecamatan Cimanggis, Depok. A quantitative approach with a survey design was employed. Data were collected from 40 pastry MSME owners between February and June 2025 using structured questionnaires and analyzed using multiple linear regression. The findings indicate that product has a positive and statistically significant effect on sales performance. In contrast, price and promotion do not exhibit significant partial effects. However, product, price, and promotion simultaneously exert a significant influence on sales performance. These results highlight the central role of product development as a core entrepreneurial strategy for value creation in pastry MSMEs, while price and promotion function as complementary strategic elements within the overall entrepreneurial decision-making process of pastry MSMEs. Academically, this study provides additional empirical evidence regarding the relationship between entrepreneurial strategic decisions and sales performance in localized pastry MSMEs.Keywords: entrepreneurship; MSMEs; pastry business; product strategy; sales performance